Multiple domain deletion towards 5’-3’ polymerase activity of DNA polymerase I from Geobacillus sp. strain SK72 - Hadrawi, Waqiyuddin Hilmi (2021)
DNA polymerases are members of family of enzyme that are essential in cellular replication and maintaining the genetic heredity of organisms. They are widely used in molecular research, especially the thermostable DNA polymerases, whereby their strong resistance to high temperatures are especially useful in DNA amplifications via the Polymerase Chain Reaction (PCR). DNA polymerase I had gained more attention in the protein-ligand interaction studies and its recent application in isothermal amplification. It is made up of three major domains that consist of a single polymerization domain and two additional exonuclease domains. Upon deletion of the N-terminal 5’-3’ exonuclease domain, the enzyme is still able to demonstrate a full polymerase activity with an additional function used in isothermal amplification. However, the center 3’-5’ exonuclease domain shows the absence of catalytic activity. The purpose of this inactive domain towards the DNA polymerase I is still unknown. Thus, in this study, a DNA polymerase I, namely, SK72 from Geobacillus sp. strain SK72 was used to understand the function of this disabled domain by studying the effect of domain deletion towards the polymerase activity. Three recombinant constructs were successfully developed based on the number of domains present. Each of the domain was identified based on the conserved regions through multiple databases such as Conserved Domain Search (CDS), InterPro Scan and Protein Families (Pfam). The regions were then analyzed to determine the appropriate first codon for each variant to prevent cutting important structures by using secondary structure prediction online tools including PSIPRED, Porter 4.0 and STRIDE. The 3D structure of each construct was predicted using YASARA software and verified against three validation tools namely ERRAT2, Verify3D, PROCHECK and QMEAN. All recombinant constructs were successfully expressed, and their proteins were purified in a single-step affinity chromatography prior to characterization. Variant SK72-Exo (large fragment without the 5’-3’ exonuclease domain) showed similar optimum temperature and pH with wild-type SK72 (with all three domains) at 60 oC and pH 9, respectively, but exhibited the highest catalytic activity followed by SK72 and SK72-Exo2. It was also able to retain 80% of its activity at 60 oC and displayed the highest helix composition among all. Meanwhile, SK72-Exo2 (without both the exonuclease domains) had the lowest polymerase activity with an optimum temperature of 40 oC and expressed pH of 7. It was the least stable amongst the variants, showing a total inactivation at 50 oC. In conclusion, the removal of 5’-3’ exonuclease domain had improved the polymerase activity and stability, while deleting both exonuclease domains had impaired the function of the polymerization domain. Thus, it is concluded that the 3’-5’ exonuclease domain might be considered as a major structural domain instead of carrying any catalytic function.